Internalisasi nilai pelestarian alam dan pendidikan karakter melalui representasi kejahatan lingkungan dalam sastra anak karya Okky Madasari - Wara Aninditari Larascintya Habsari (Universitas Mulawarman, 2023)
The subject of this research is Mata dan Rahasia Pulau Gapi by Okky Madasari. I adopt green cultural criminology and narrative criminology to analyze how the writer describes environmental crime phenomena in her work as a medium for internalizing the value of conservation and character education for children’s readers. This study was designed using the children's literature research method and note-taking technique. The results of this study found that the novel contains two forms of environmental crimes, namely crimes against historical sites and crimes against wildlife. I also found that the author makes the representation of the character's resistance to environmental crimes as a strong message to readers that children have a role as agents to encourage public awareness of environmental issues. In addition, moral licensing by the perpetrators of environmental crimes in this novel is the author's effort to cultivate a critical attitude in child readers.